First‐in‐human clinical trial to assess pharmacokinetics, pharmacodynamics, safety, and tolerability of iscalimab, an anti‐CD40 monoclonal antibody. Issue 2 (6th December 2019) - Espié, Pascal; He, YanLing; Koo, Phillip; Sickert, Denise; Dupuy, Cyrielle; Chokoté, Edwige; Schuler, Roland; Mergentaler, Heidi; Ristov, Jacinda; Milojevic, Julie; Verles, Aurelie; Groenewegen, Andrea; et al.
Abstract : Iscalimab is a fully human, CD40 pathway blocking, nondepleting monoclonal antibody being developed as an immunosuppressive agent. We describe a first‐in‐human, randomized, double‐blind, placebo‐controlled study investigating the safety, tolerability, pharmacokinetics, and pharmacodynamics of iscalimab in healthy subjects and rheumatoid arthritis patients. Healthy subjects (n = 56) received single doses of intravenous iscalimab (0.03, 0.1, 0.3, 1, or 3 mg/kg), or subcutaneous iscalimab (3 mg/kg), or placebo. Rheumatoid arthritis patients (n = 20) received single doses of intravenous iscalimab (10 or 30 mg/kg) or placebo. Iscalimab exhibited target‐mediated drug disposition resulting in dose‐dependent and nonlinear pharmacokinetics. Complete (≥90%) CD40 receptor occupancy on whole blood B cells was observed at plasma concentrations >0.3‐0.4 µg/mL. In subjects receiving 3 mg/kg iscalimab, antibody responses to keyhole limpet hemocyanin were transiently suppressed. CD40 occupancy by iscalimab prevented ex vivo human rCD154‐induced expression of CD69 on B cells in whole blood. All doses were generally safe and well tolerated, with no clinically relevant changes in any safety parameters, including no evidence of thromboembolic events. Iscalimab appears to be a promising blocker of the CD40‐CD154 costimulatory pathway with potential use in transplantation and other autoimmune diseases. Abstract : Iscalimab is a promising blocker of the CD40‐CD154 costimulatory pathway with potential use in transplantation and autoimmune diseases.